Airline service quality: Malaysia low cost airline / Mohd Iqmal Mustapha - Mustapha, Mohd Iqmal (2013)
The Malaysian airline sector has become increasingly competitive in the past decade especially in the low cost carrier industry. The growing competition has prompted the airline management to focus on generating favorable customers' perceptions of their service as favorable perceptions encourage repeat purchase. It is very important for the airline to retain existing customers and attracting new customers to ensure they remain profitable in the Malaysia aviation industry. Upon the preliminary stage of this study, the researcher found a limited conceptual gap in marketing literature as there has very limited been publishing research on service quality, customer satisfaction or behavioral intentions on the low cost airline industry in Malaysia. By identifying the dimensions of service quality, and empirically examining the interrelationships among the service quality, passenger satisfaction and behavioral intentions, this study hopefully will fill the gap found. The purpose of this study is to empirically identify and examine the relationships of service quality dimension, satisfaction, and behavioral intentions in passengers of low-cost carriers in Malaysian market. A sample of 272 passengers who had travelled on LCCs in Malaysia few hours after their flight are surveyed in order to identify the sub-dimensions of service quality in Malaysia and test hypothesised relationships among the constructs of service quality, satisfaction, and behavioral intentions. The data were analyzed using exploratory factor analysis and multiple regression analysis.Using exploratory factor analysis , the study finds the importance of the dimensions of service quality such as; assurance, aircraft tangibles, personal, terminal tangibles, special offers and freebies, reliability, and ground service contribute to their satisfaction level of low cost airline in Malaysia. The result of regression analysis revealed that the passenger satisfaction with the service-quality dimensions that were found in this study showed to be very important in explaining behavioral intentions. Satisfied passengers are mostly influenced by airport tangibles, personnel professionalism and ground arrangement. Such customers engage in positive word-of mouth communication have fairly repurchase intentions. This study provides a framework in understanding the effects of the proposed service quality sub-dimensions of satisfaction and behavioural intentions of low cost airline in Malaysia. Satisfaction was also supported as a mediating effect on the relationship between service quality and behaviour intentions. Practically, the research will benefits the manager in understanding of perceived passengers importance of the service quality of their airline, the level of satisfaction and behavioural intentions off a low cost carrier in Malaysia.